What Should Schools Teach? Disciplines, subjects and the pursuit of truth - Sehgal Cuthbert, Alka; Standish, Alex (Knowledge and the Curriculum, 2021)
The design of school curriculums involves deep thought about the nature of knowledge and its value to learners and society. It is a serious responsibility that raises a number of questions. What is knowledge for? What knowledge is important for children to learn? How do we decide what knowledge matters in each school subject? And how far should the knowledge we teach in school be related to academic disciplinary knowledge? These and many other questions are taken up in What Should Schools Teach? The blurring of distinctions between pedagogy and curriculum, and between experience and knowledge, has served up a confusing message for teachers about the part that each plays in the education of children. Schools teach through subjects, but there is little consensus about what constitutes a subject and what they are for. This book aims to dispel confusion through a robust rationale for what schools should teach that offers key understanding to teachers of the relationship between knowledge (what to teach) and their own pedagogy (how to teach), and how both need to be informed by values of intellectual freedom and autonomy. This second edition includes new chapters on Chemistry, Drama, Music and Religious Education, and an updated chapter on Biology. A revised introduction reflects on emerging discourse around decolonizing the curriculum, and on the relationship between the knowledge that children encounter at school and in their homes. Praise for What Should Schools Teach? 'This book brings profound questions about what children need to know back to the centre of educational enquiry where they belong. The additional chapters in this second edition are excellent. We all need to read it.' Professor Elizabeth Rata, University of Auckland 'I am afraid that what we actually teach is so often forgotten in debates about schools. Subjects - the way that most people choose to divide up human knowledge - are too rarely the focus of our interest. Yet the subjects we offer and the syllabus content of each is arguably the most important single element of the school system. This book bucks the trend and should be of great importance to all teachers.' Barnaby Lenon, University of Buckingham